Design and test of a resonance control system for suppressing the pump vibration effects for the PEFP 13-MHz RF cavity - Trịnh, Thị Tú Anh (2023)
The Proton Engineering Frontier Project developed a 13-MHz pulsed, RF cavity for heavy-ion implanter applications. Typically, slow changes in the room temperature and the mechanical vibrations of the vacuum device may be primary sources of disturbances, and the accelerating cavity of the implanter may not be able to operate at the resonance frequency owing to disturbance effects. We need a voltage-controlled oscillator phased-locked loop circuit to make a control system that could suppress the disturbance effects; thus, the accelerating gradient of the cavity always reached a peak level for a given input power and coupling. An analog-circuit-based RF-frequency-tracking system was developed. Next, we obtained the optimal control parameters for the key control components. Finally, we measured the system performance between an open loop and a closed loop. The key point of the system design is to control the driving frequency that is used to operate the RF source by keeping the phase at around 0 degrees with respect to the resonance peak of the cavity. The experimental results showed that the fluctuations of the control loop error signal were suppressed by about a factor of 10. The presented feedback loop is implemented as a standard proportional controller. The loop p-gain is 120 k.